Oxidative stress damage in the protozoan parasite Trypanosoma cruzi is inhibited by Cyclosporin A - Bustos, Patricia L. (2015)
Fil: Bustos, Patricia L. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.